The life of Augustine. - Le Nain de Tillemont, Louis-Sébastien, 1637-1698 (Collectanea Augustiniana., 2010)
In 1695, Louis Sébastien, Le Nain de Tillemont completed volume 13 of his Mémoire ecclésiastique, a work of 1200 pages published posthumously in 1700. This was the first modern biography of Augustine, and the most comprehensive of all Augustinian biographies. This English translation has been divided into three volumes.